Boundary Effect Modeling In the Problem of Stochastic Heterogeneous Stripe Tension Under Creep - L. V. Kovalenko; N. N. Popov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2009)
The boundary effect in stochastic creep boundary problem of endless heterogeneous stripe tension was modeled. Determining creep factors which were applied in compliance with a nonlinear theory of viscid flow are formulated in a stochastic form. The problem is solved approximately with disturbance method related to tensions tensor component. Statistical analysis was performed on the basis of solution allowing defining the basic features of boundary effect.